Analysis of Reading Comprehension Skills of Elementary School Students - Silvia, Shinta; Damayanti, Vismaia S (International Conference on Elementary Education, 2025)
This study was motivated by the low reading comprehension skills of SDN 2 Cirapuhan students. The purpose of this study is how the reading comprehension skills of students in grade VI SDN 2 Cirapuhan and what are the obstacles experienced by students in reading comprehension. This study used descriptive qualitative research with the research subjects being grade VI students. The instruments used in this research are tests and interviews where to collect data and find information related to the problem as a form of research report results. Based on the results of the study, it can be concluded that the results of the reading comprehension ability test of class VI SDN 2 Cirapuhan obtained an average score of 58 which is included in the category of less and the results of the interview show the factors that become obstacles for students in reading comprehension, namely lack of motivation and student interest, environmental influences, inappropriate learning models or methods and inadequate reading materials.